Towards a predictive capability for the resuspension of particles through extension and experimental validation of the Biasi implementation of the "Rock'n'Roll" model. (November 2019) - Vincent, Jack C.; Hill, Jonathan; Walker, Maurice D.; Smith, Simon A.; Smith, Sarah E.; Cant, Nicola E.
Abstract: When considering the behaviour of particulate materials in the environment, it is important to consider resuspension, in which deposited particles leave the ground and become airborne. Despite significant study, models of resuspension typically include no treatment of transient phenomena in the period shortly after release. This paper describes the selection, initial implementation and validation of a resuspension model that is suitable for the stepwise introduction of real-world complexity (such as the effects of humidity, particle shape, roughness or composition), thus enabling it to be developed from simplistic, idealised scenarios to real particles and surfaces. Using an adapted version of the Biasi, de los Reyes, Reeks, and De Santi (2001) implementation of the "Rock'n'Roll" model for resuspension proposed by Reeks and Hall (2001), results for resuspension of hard smooth spherical particles from hard smooth surfaces under dry conditions were modelled. These were found to agree to within an order of magnitude in all cases, and typically within a factor of two, with experimental data for the proportion of particles resuspended as generated using a custom built highly controllable wind tunnel. To the authors' knowledge, this is the first time that reproducible data, suitable for model validation for particles of respirable size under commonly expected environmental conditions, has been collected. As proof of principle of the stepwise approach to the introduction of complexity, the model was adapted and extended to include capillary forces. This enabled experimental confirmation that the model was able to predict correctly the effect of relative humidity on resuspension. Results demonstrated that the level of agreement between model and experiment has been maintained. Graphical abstract: Image 1 Highlights: Mechanistic resuspension model developed for hazard prediction applications. Model designed and implemented for stepwise introduction of complexity. Experimental validation obtained for glass beads in custom-built precision-controlled wind tunnel. Agreement achieved to within an order of magnitude, typically within factor of ∼2. Effect of airborne humidity introduced into model and subjected to validation.